Latin American and Spanish-speaking perspectives on the challenges of global psychiatry - Renato D. Alarcón; Fernando Lolas; Jair J. Mari; José Lázaro; Enrique Baca-Baldomero (Brazilian Journal of Psychiatry)
The multi-faceted phenomenon known as globalization has a particular impact on the conceptual and practical development of mental health disciplines in general, and psychiatry in particular, across different world regions. To be theoretically and functionally effective, global psychiatry requires an integration of its different components. To such objective, and after a brief review of continental European and Anglo-Saxon contributions, this article examines the history, characteristics, and contributions of Latin/Iberian American and Spanish-speaking psychiatry, in order to substantiate its role in world psychiatry. The Latin American proper (including Portuguese-speaking Brazil), Spain, and U.S.-based Hispanic components are described, revealing an identity that is based on a humanistic tradition, a value-based, culturally-determined clinical approach to patient care, and a pragmatic adaptation of different treatment resources and techniques. These may constitute supportive elements of an instrumental inter-regional bond in the present and future of our discipline.